Begin where you are: the Colorado poets laureate anthology - Wyatt, Turner, compiler; Crow, Mary, editor; Gibson, Andrea, editor; Hutchison, Joseph, editor; LeFebre, Bobby, editor; Mason, David, editor; Seldin, Julia, editor; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2025)
Begin Where You Are: The Colorado Poets Laureate Anthology is a book of firsts. It is the first ever US state poet laureate anthology. It is the first poetry collection featuring all ten Colorado poets laureate (the second oldest state poet laureateship, established in 1919). And it is the first place readers can discover unpublished poems by Andrea Gibson-bestselling author and one of the most influential spoken word artists of our generation. This book contains celebrated works from Thomas Hornsby Ferril and others, alongside never-before-published pieces from Bobby LeFebre, Joseph Hutchison, David Mason, and Mary Crow. Contemporary poets offer perspectives on how serving as Colorado poet laureate shaped their writing and worlds.--Provided by publisher.
Featured poets include Andrea Gibson (laureate 2023-2025), Bobby LeFebre (laureate 2019-2023), Joseph Hutchison (laureate 2014-2019), David Mason (laureate 2010-2014), Mary Crow (laureate 1996-2010), Thomas Hornsby Ferril (laureate 1979-1988), Milford E. Shields (laureate 1954-1975), Margaret Clyde Robertson (laureate 1952-1954), Nellie Burget Miller (laureate 1923-1952), and Alice Polk Hill (laureate 1919-1921).
Keywords: American poetry -- Colorado -- 20th century; American poetry -- Colorado -- 21st century; Poets laureate -- Colorado